Internalizing Problems of Youth Involved in Bullying via Different Participant Role Combinations and Gender. Issue 3 (1st September 2019) - Tennant, Jaclyn E.; Klossing, Jacqueline J.; Demaray, Michelle K.; Dorio, Nicole; Bixler, Trevor; Jones, Caicina
Abstract: The purpose of the current study was to identify how defending behaviors in bullying overlap with bullying behaviors and victimization experiences using an empirical approach. Furthermore, an additional goal was to examine internalizing problems associated with these bullying role behaviors. Data on students' defending and bullying behaviors, victimization experiences, anxiety, depression, and self-esteem were collected from 700 sixth- through eighth-grade students using the Bully Participant Behaviors Questionnaire, the Screen for Child Anxiety Related Disorders–Child Version, the Center for Epidemiological Studies–Depression, and the Rosenberg Self-Esteem Scale. Results of a latent profile analysis identified the following roles: defenders, bully–victim–defenders, and students who had low involvement in bullying, victimization, and defending. Results documented significant differences in internalizing problems among the roles. Specifically, bully–victim–defenders reported higher levels of depression and anxiety and lower levels of self-esteem than did defenders and students who had low involvement with bullying scenarios.